Vpliv tenisko motoricnih sposobnosti in temeljnih antropometricnih znacilnosti na tekmovalno uespesnost mladih teniskih igralik in igralcev - Filipcic, A.; Filipcic, T.; Leskosek, B. (Kinesiologia Slovenica, 2004)
The aim of the present research is to find out how selected variables (explosive power of the arms, elastic power of the legs, repetitive strength of the trunk, movement speed, speed of alternative arm movements, agility, dynamic balance, flexibility of the shoulder girdle, running endurance, body height and body weight) can be used to explain the variance of criterion variable, represented by competition successfulness. The tests of tennis motor abilities and anthropometric measurements were carried out on a sample of 51 female and 52 male tennis players, aged 13. A regression analysis of female and male tennis players was carried out. It showed that the system of tennis motor variables explains 49% of the variance of criterion variable in female tennis players, and 54% in male tennis players. For female tennis players three variables were extracted that seem statistically significant for explaining the variance of criterion variable: the tests of elastic leg power, balance and running endurance; in the case of male tennis players two variables seem statistically significant. These two variables are the test of agility (fandrill) and body height. The findings indicate that the results of tennis motor tests and anthropometric measurements should be valued differently for female and male tennis players of the same age.